PROBLEM-BASED LEARNING AS A FACILITATOR OF STUDENTS’ READING COMPREHENSION - Satriani, Satriani; Hasbi, Muhammad; Amiruddin; Fahirah, Ainun (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to determine to what extent the Problem-Based Learning method improved reading comprehension during the second year of MA Muhajirin As'adiyah Kampiri. This study employed a pre-experimental approach to attain its goal. The researcher employed a cluster random sampling technique with a sample of 24 students from classes XII-A. The pre-test and post-test were used to collect data. Problem-Based Learning was used to teach the experimental class. The data was analyzed using the education data analysis formula. The pre-test and post-test results revealed a considerable improvement. It was demonstrated by the fact that the mean score of the students' experimental post-test (77.9) was greater than the mean score of the students' pre-test (41.8), and the post-test T-test value was 0.02, which was less than (α) = 0.05. The treatment causes an improvement in kids' reading comprehension. Problem-Based Learning improves students' thinking skills and encourages them to use their abilities to read literature. So that students participating in Problem-Based Learning could easily understand the texts. As a result, it is concluded that implementing problem-based learning improves students' reading comprehension throughout their second year of MA Muhajirin As'adiyah Kampiri.